Analisis Faktor-Faktor Mempengaruhi Kinerja Karyawan Pada PT Global Transportasi Nusantara Semarang - Priyono, Edi; Bala, Rima Parawati; Nugroho, Totok Susilo Pamuji (Jurnal Ilmiah Raflesia Akuntansi, 2024)
-This study aims to determine, analyze and empirically prove the influence of work motivation, work environment, and work loyalty on employee performance at PT. Global Transportasi Nusantara. The analysis technique in this study consists of instrument testing: validation test & reliability test, classical assumption test (normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression analysis, t-test, F-test and R2 test (determination coefficient test). The results of the t-test indicate that: Work motivation has a positive and significant effect on employee performance. The work environment has a positive and significant effect on employee performance. Work loyalty has a positive and significant effect on employee performance. The results of the F-test can be concluded that together the variables of work motivation, work environment, and work loyalty have a significant effect on employee performance. The determination test with an Adjested R Square value of 0.788 means that the performance of employees at PT. Global Transportasi Nusantara can be explained by the variables of work motivation, work environment, and work loyalty by 22.2%.